Respostas

2014-08-19T12:00:36-03:00
4x²-27-x²
4x²-x²=27
3x²=27
x²=27/3
x²=9
x=v9
x=3
1 5 1
2014-08-19T12:37:49-03:00
4 x^{2}  - 27 =  x^{2}  \\  \\ 4 x^{2}  -  x^{2} -27 = 0 \\  \\ 3 x^{2} -27 = 0

Resolvendo por Bhaskara.

x = \frac{-b \pm \sqrt{b^2 -4*a*c}}{2*a}

a = 3, b = 0, c = -27

Δ=b2−4ac
Δ=(0)2−4*(3)*(−27)
Δ=0+324
Δ=324

x = \frac{-b \pm \sqrt{\triangle}}{2*a}
x = \frac{0 \pm \sqrt{324}}{2*3} \\  \\ x = \frac{0 \pm 18}{6} \\  \\ x' = \frac{0 + 18}{6} \\  \\ x' = \frac{18}{6} \\  \\ x' = 3 \\  \\  \\ x'' = \frac{0 - 18}{6} \\  \\ x'' = \frac{-18}{6} \\  \\ x'' = -3

S  = {3, -3}